(untitled) (Journal of Decolonising Disciplines, 2020)
This paper considers the domain of subjectivity and knowledge in the colonial matrix of power and its relation to the university. It explores how this subset of the said matrix has led to the (social) death of students, specifically Black students, within the contemporary westernised university in the South African context. I maintain that the colonial matrix of power which defines the westernised university gives rise to violence, as students attempt to escape (social) death and regain their humanity. Furthermore, student responses to institutional violence (symbolic, systematic and subjective), which imposes a state of (social) death on Blackness, are delegitimated through the discourse of irrationality and vandalism, and reproduce the problematic discourses that relegate Blackness to the social position that imposes (social) death in the first place. My aim in this paper is thus to explicate this colonial matrix of power as it plays out in the university context.